Sensitivity and Specificity of Electroencephalography (EEG) Among Patients Referred to an Electrophysiology Lab in Bangladesh (Journal of Dhaka Medical College, 2015)
Objective: To measure the changes in electro encephalogram (EEG) along with its sensitivity and specificity with clinical seizure among epilepsy patients referred to an electrophysiology lab in a tertiary care hospital of Bangladesh.Methods: This retrospective chart review was carried out in the electrophysiology laboratory of Dhaka Medical College Hospital from January 2011 to December 2013, which included 1154 patients. EEG was obtained through scalp electrodes following international 10/20 system. Information regarding patients was collected from the laboratory register with the help of a checklist. The EEG findings and clinical seizure events were then compared.Result: Among the 1154 patients, age varied from birth to 75 years. The mean age at presentation was 17±11.4 years and most of the patients were less than 10 years old (44.4%). The male predominated in our study (59.2%). Clinically diagnosed seizure was present in 970 patients (84.1%), among which Generalized tonic clonic seizure (GTCS) was the most common clinical type of seizure, followed by secondary generalized seizure in 19.4% (n=224) and focal seizure in 2% (n=30) patients and 6.8% (n=79) patients had pseudoseizure. Among the abnormal EEG (59%), generalized epileptiform discharge was found in 29%, whereas focal and secondary generalized discharge was found in 30%. The most common site of origin of epileptiform discharge was temporal lobe (28.3%). The overall sensitivity of EEG was 66% (ranged from 62% to 68% with a confidence interval (CI) at 95%) and specificity was 79% (72- 84% at 95% CI). The positive predictive value was 58% (55-61% at 95% CI) and negative predictive value was 41% (38-44% at 95% CI).Conclusion: Our study brings out the fact that EEG has a reasonable sensitivity and specificity as a diagnostic test and the superiority being the higher specificity of EEG.J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 215-222